ANALISIS PENDAPATAN USAHA OLAHAN SAGU (METROXILYON) DI UD SAGU PEMAKUAN DESA PEMAKUAN KECAMATAN SUNGAI TABUK KABUPATEN BANJAR - Fenny Refiana; Eddy Ttriatmoko; Subhan Fitriadi (Chlorophyl, 2020)
The purpose of this research is to know the revenue,the eksplicit cost and the income of make Sagu farming . This research was conducted in April 2020 at village Pamakuan, sungai Tabuk, Banjar regency province South Kalimantan . The studi case metode used was by observing UD Sagu Riza in Pamakuan Sei Tabuk who.make Sagu. The Average result of the revenue is Rp.36.750.000 / month, the average Eksplicit cost is Rp.27.436.148,00/month, and Average income Rp.9.313.852,00/month . From this result of development of farming make sagu we believe that it has good prospect and revenue, of the average income ,tecnicall and economically..